Diagnosis of Physical Education Teachers Welcoming Industry 5.0 Using the TDC Method - Smith, George; ., Saputro; ., Primajaya (KnE Social Sciences, 2023)
The purpose of this study is to understand the challenges faced by the physical education teachers, nowadays, in industry 5.0. The method used was the IT literacy survbey along with Teacher Digital Competence (TDC). Meanwhile, qualitative research was done by distributing questionnaire and tests knowledge to 103 students of Internal Teacher Professional Education Position 2022. The sample selection technique used was purposive sampling, based on purpose and availability sample for inspection. Results were obtained from technical competence 77.38% mastered, while 22.62% did not master; content knowledge competence 69.91% who answered correct and 31.09 answered incorrect; pedagogical and learning design competence 39.89% implemented, 60.1% did not implement in learning. Based on the data above that required enhancement competence, skills-based technology is suggested for welcome industry 5.0. Keywords: physical education, industry 5.0, tda method